Breaking the Cycle of Injustice: Revolutionizing Human Rights Violations Resolution Through the 1945 Constitution - Amancik Amancik; Putra Perdana Ahmad Saifulloh; Ali Masyhar; Asrul Ibrahim Nur; Sonia Ivana Barus (Universitas Negeri Semarang, 2024)
The stagnation of human rights enforcement in Indonesia's Reformation Era has highlighted a critical imbalance: the current system prioritizes punishing perpetrators of serious human rights violations over addressing the recovery and well-being of victims. This research introduces The Constitution of Peace as a transformative, victim-centered model for resolving serious human rights violations outside the courtroom, aligning with the principles and soul of the 1945 Constitution. The proposed model comprises three innovative approaches: first, mediation facilitated by the National Human Rights Commission to foster dialogue and accountability; second, the provision of compensation, restitution, and assistance to victims through the Witness and Victim Protection Agency, ensuring tangible support for recovery; and third, an official apology by the relevant authority, accompanied by the fulfillment of economic, social, and culpability obligations. Together, these measures aim to correct the limitations of the current retributive framework by prioritizing restorative justice and victim empowerment. By embracing these victim-oriented solutions, this model not only addresses the legal and moral obligations enshrined in the 1945 Constitution but also fosters reconciliation and societal healing. The research underscores the transformative potential of the Constitution as a foundation for peace, justice, and the resolution of entrenched human rights challenges. It calls for a paradigm shift from punitive measures to a more holistic approach, ensuring that justice serves both the dignity of victims and the broader goal of national harmony.